Cystic hypersecretory ductal carcinoma (CHDC): a rare distinctive variant of ductal carcinoma. Issue 7 (21st July 2021) - DiPasquale, Ashley; Peiris, Lashan; Silverman, Svetlana
Abstract : Cystic hypersecretory ductal carcinoma (CHDC) is a rare distinctive variant of ductal carcinoma that behaves in a low-grade fashion. This rare form of breast malignancy has only been reported a handful of times in the surgical literature. This article outlines the clinical presentation, workup and management of a 43-year-old woman who presented with a bilobed cystic mass of the right breast diagnosed as CHDC.